Pengaruh Penggunaan E-Filing dan E-SPT Terhadap Pelaporan E-SPT Oleh WPOP Yang Terdaftar Di Wilayah Kabupaten Bogor - Nur Sabila Yassarah; Rahmat Mulyana Dali (Komunitas Dosen Indonesia, 2023)
The purpose of this study was to determine the effect of using E-Filing and E-SPT partially and simultaneously on E-SPT reporting by registered individual taxpayers (WPOP) in the Bogor Regency area. Research by quantitative descriptive research methods, individual taxpayers with the type of work employees of Stated-Owned Enterprises (BUMN), civil servants and private employees who are registered at the Primary Tax Service Office (KPP) in the Bogor Regency area will be an object of research. The number of samples used in this study were 100 respondents who were calculted based on the slovin method formula with the method of determining the sample, namely accidental sampling or called convenience sampling. Data collection was carried out by distributing questionnaires and observing then analyzed using multiple resgression analysis techniques with SPSS 22.0 version. The results of this study indicate of E-Filing partially has no significant and positive effect on E-SPT reporting, the use of E-SPT partially has a significant positive effect on E-SPT reporting and the use of E-Filing and E-SPT simultaneously has a significant positive effect on E-SPT reporting.